Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak, dan Tax Amnesty Jilid II pada Kepatuhan WP OP di KPP Pratama Badung Selatan - Hardi, Helen Triandini; Jati, I Ketut (Jurnal Ilmiah Wahana Pendidikan, 2025)
Taxpayer participation in tax payment is important so that national development can be carried out, however there are major obstacles faced by Directorate General of Taxes in tax collection that is tax compliance. The level of Indonesian tax compliance can be seen from the tax ratio figure and taxpayer compliance in reporting tax returns. Tax compliance in Indonesia assessed by the level of tax ratio shows that Indonesia's tax ratio is lower when compared to ASEAN countries such as Thailand, Vietnam, and Singapore. Similar with the level of reporting tax returns in Indonesia has decreased in 2022. The purpose of this study to examine the influence of taxpayer awareness, tax sanctions, and tax amnesty volume II on individual taxpayer compliance at KPP Pratama Badung Selatan. The sampling method used simple random sampling. The samples size were determined using the Slovin formula so that 78 respondents were obtained. The survey method through questionnaires is used in collecting data. The technique of data analysis in this study used multiple linear regression analysis. This study found that taxpayer awareness and tax amnesty volume II have no effect on individual taxpayer compliance, while tax sanctions have a positive effect on individual taxpayer compliance.